Reframing “the most holy spot in Ireland”: an analysis of the narratives from and around Kilmainham Gaol (Altre Modernità, 2022)
Prisons play a prominent role in Irish imagination and collective memory, because their wings and cells bore witness to many turning points in the country’s recent history. Kilmainham Gaol, often called ‘the Bastille of Ireland’, is no exception: from 1796 to its closure in 1924, it held the leaders of nineteenth-century agrarian and nationalist revolts as well as the Easter Rising rebels in 1916. Given the Gaol’s importance in nationalist history, it has been argued that a specific narrative came to be constructed around it by its restorers: one aimed at elevating the Gaol to a symbol of the separatist struggle, and which deliberately downplayed the fact that the prison had been a place of detention also for non-political prisoners and the opponents of the Free State. Scholars contend that this narrative long dominated over stories of ordinary penal history, and, only recently, brief mentions of ‘ordinary’ prisoners and the Civil War have entered the dominant narrative. My article questions these assumptions and is divided into two parts to outline such ‘reframing’ of Kilmainham Gaol: first, drawing on archival documents, I discuss the intention of the authorities to redesign Ireland’s past as a monolithic history of struggle against the enemies of the nation in their narrative of the Gaol, and I argue for the need to consider their reasons to do so; second, I resort to Witcomb’s methodological approach to highlight how today’s curators respond to the representational challenges posed by the Gaol and aim at incorporating into the narrative of the site the dissonant voices of those who had been previously neglected.